Trust in negotiation - Lewicki, Roy J. (Henry Stewart Talks, 2013)
Why we negotiate, Exchange of information, Importance of trustworthiness and trust, Credibility, Diplomacy, Honesty, Consequences of absent or broken trust, Dilemma of trust, Dilemma of honesty, Managing the dilemmas, Competence, Integrity, Trust violations, Trust repair, Verbal accounts, Apologies, Reparations, Structural solutions, Verification, Monitoring